Loss of TRPV4 is insufficient to promote repair in a spinal cord injury contusion model - Melanie Mertens; Sofie Kessels; Naomi Veeningen; Elle E. M. Scheijen; Femke Mussen; Amber Delbroek; Jana Van Broeckhoven; Yeranddy A. Alpizar; Bert Brône (Scientific Reports)
Abstract Microglia, the primary phagocytes activated after spinal cord injury (SCI), play a key role in containing the lesion and protecting the glial scar from infiltrating immune cells. Although these responses are initially protective, excessive microglial proliferation and sustained pro-inflammatory activation can worsen secondary damage and limit recovery. Modulating microglial activity has been proposed as a potential therapeutic approach to enhance SCI repair. Previous studies suggest that constitutive loss of the mechanosensory channel TRPV4 (transient receptor potential vanilloid 4) reduces microgliosis and inflammation at the lesion site, improving functional outcomes. TRPV4 is a Ca2+-permeable channel implicated in several microglial characteristics, like morphology, motility, proliferation, and phagocytosis. Whereas endogenous TRPV4-activating stimuli are abundant at the lesion site, the microglia-specific contribution of TRPV4 in SCI recovery remains unknown. To investigate this, we used phagocyte-specific Trpv4 conditional knockout mice and phagocyte-specific TRPV4-deficient bone marrow chimeras subjected to contusion SCI. We achieved robust and efficient spinal cord monocyte-derived cell repopulation after bone marrow transplantation and PLX treatment. Surprisingly, TRPV4 deficiency in phagocytes did not enhance functional recovery, reduce microgliosis, or diminish scar formation after SCI. Furthermore, contrary to prior studies, constitutive TRPV4 deficiency did not improve SCI outcomes, indicating that the role of TRPV4 in this context is complex and potentially redundant with other pathways.